Analisis Laporan Keuangan Untuk Mengukur Kinerja Keuangan PT. Intan Segara Semarang Dalam Pandemi Covid-19 - Bayu Teguh Wibowo (LPPM STIE Anindyaguna, 2020)
The Covid-19 virus pandemic has put a lot of pressure on the economy as well as businesses. Financial statement analysis is used to measure the financial performance of PT Intan Segara Semarang during this pandemic. The purpose of the study was to determine the performance of PT Intan Segara Semarang in the Covid-19 pandemic seen from the liquidity ratio, solvency ratio, activity ratio and profitability ratio. The data used is primary data, namely the Balance Sheet and Profit and Loss Statements for 2020 and the previous 2 years, namely in 2019 and 2018. Using qualitative and quantitative analysis, it is obtained that PT Intan Segara has good financial performance, assets and capital that is able to support company performance and low debt levels so that performance remains good during the Covid-19 virus pandemic.